Screening of Fabry disease in patients with chronic kidney disease in Japan. Issue 1 (19th July 2021) - Nagata, Akiko; Nasu, Makoto; Kaida, Yusuke; Nakayama, Yosuke; Kurokawa, Yuka; Nakamura, Nao; Shibata, Ryo; Hazama, Takuma; Tsukimura, Takahiro; Togawa, Tadayasu; Saito, Seiji; Sakuraba, Hitoshi; et al.
Abstract: Background: Fabry disease (FD), an X-linked lysosomal storage disorder caused by a deficiency in alfa-galactosidase A (α-Gal A) activity due to mutations in the GLA gene, has a prevalence of 0–1.69% in patients undergoing haemodialysis; however, its prevalence in patients with chronic kidney disease (CKD) Stages 1–5 is unknown. Methods: Serum α-Gal A activity analysis and direct sequencing of GLA were used to screen for FD in 2122 male patients with CKD, including 1703 patients with CKD Stage 5D and 419 with CKD Stages 1–5. The correlation between serum α-Gal A activity and confounding factors in patients with CKD Stages 1–5 was evaluated. Results: FD prevalence rates in patients with CKD Stage 5D and CKD Stages 1–5 were 0.06% (1/1703) and 0.48% (2/419), respectively. A patient with CKD Stage 5D exhibited a novel GLA mutation, p.Met208Arg, whereas two patients with CKD Stages 1–5 had c.370delG and p.Met296Ile. p. Met208Arg caused moderate structural changes in the molecular surface region near the substituted amino acid residue but did not affect the catalytic residues Asp170 and Asp231 in α-Gal A. Serum α-Gal A activity in patients with CKD Stages 1–5 was inversely correlated with age (P < 0.0001) but directly correlated with estimated glomerular filtration rate (P < 0.0001). Conclusions: FD prevalence was much higher in male patients with CKD Stages 1–5 than in those with CKD Stage 5D. FD screening in patients with CKD Stages 1–5 may improve patient survival, decreasing the number of patients with CKD Stage 5D.